Studi komparasi antara model pembelajaran direct instruction dan model pembelajaran mind mapping terhadap keterampilan menulis karangan deskripsi ditinjau dari motivasi belajar pada peserta didik kelas V Sekolah dasar - Tyastiningsih Tyastiningsih; Slamet Slamet; Sukarno Sukarno (Didaktika Dwija Indria, 2019)
Abstrac: The purpose of the research to know defferences of (1) Direct Instruction and Mind Mapping models influence towards student writing skill disciption text. (2) leraning motivastion influence in high and low category toward student writing skill disciption text, (3) the effect interaction of leraning-model implementation and leraning-motivastion toward writing skill description text. The samples of the research are Grade V SD N Musuk 1 and grade V SD N Sukorame 1. This  research use experimental method with 2x2 factorial design. Data were collected by means of questionnaire for students learning motivation data and test for the data of students writing skill description text. Those data were analyzed with two-way Anava test with different content of cell, followed with double comparison of Scheffe method whit level of significance 0,05. The result showed that, frist there were significance difference between Dirct Instruction and Mind Mapping model’s toward students writing skill disciption text (FA = 9,85 > Ftabel = 2,8.). second, there were significance difference between learning motivation influence in high and low toward student writing skill description text (FB = 2,88 > Ftabel = 2,8. Third, there was no effect interaction of learning-model implementation and leraning-motivation toward writing skill description text (FAB = 0,02 < Ftabel = 2,8). Keywords : Direct Instruction, Mind Mapping, Learning Motivation, Writing Skill